Consumption Patterns of Trans-Fat Products among undergraduates of University of Nigeria Nsukka - Glory Uchechi Eze; Eunice Ifenyinwa Ugwu (International Journal of Home Economics, Hospitality and Allied Research)
This study investigated Consumption Patterns of Trans-Fat Products Among Undergraduates of University of Nigeria, Nsukka. There were three research questions that guided the study. The study adopted a descriptive survey design. The population used for the study comprised 41107 undergraduate students in University of Nigeria, Nsukka for the 2019/2020 academic session. Krejcie & Morgan sampling formula was used to draw a sample of 380 undergraduate students from the population which were studied. Data collection was facilitated using a structured students’ questionnaire on consumption patterns of trans-fat products (SQCPTFP) developed by the researcher. The instrument was face validated by three experts for internal consistency and credibility. The estimates of internal consistency of the developed scales were determined using Cronbach alpha based on the data collected in a pilot study among 30 undergraduate students outside the area of the study. The overall reliability estimate obtained was 0.856 for the entire 43 items. The findings of the study revealed that 100% of the respondents agreed to be consuming trans-fat products, hence there is no significant difference in the types of trans-fat products consumed by students based on their gender; respondents have a limited budget for better food, lack of time to cook, non-availability of healthy foods, cost of eating healthy foods, and trans fat products taste better; finally, the study revealed some suggested ways through which trans-fat consumption can reduced among undergraduates. Based on these findings, it was recommended that the students’ curriculum should include the health impact of these trans-fat products consumption to create the knowledge in the students.